Intervensi Latihan Sensori Motorik Dalam Pengembangan Kinestetik Anak Autis - Zonalisa Fhatri (Tarbawy : Jurnal Pendidikan Islam, 2020)
Abstract Based on data released by the Central Bureau of Statistics, the number of autism in Indonesia in 2010 is estimated to reach 2.4 million people. In that year, the population of Indonesia was 237.5 million people with a growth rate of 1.14 percent. The number of people with autism in Indonesia is estimated to have an increase of about 500 people every year. It is necessary to make efforts to hone the special skills of children with autism that adjust to the stage of its development. The development includes all aspects of language development, social, emotional, and physical development of the child's motor. Professionals often focus on emotional, social, and family issues only whereas motor development is also an integral part in the life of an autistic child. Based on the data source, this research is a field research using qualitative research methods that is analyzed descriptively. The number of subjects in this study is 5 children. Respondents were taken based on purposive sampling. The data collection techniques used interviews, observation, and documentation and the data was analyzed using data reduction, data presentation, and conclusion. The results of this study indicated that the sensory integration (SI) exercise includes 7 areas namely, vestibular, tactile, propioceptive, visual, auditory, gustatory, and olfactory. Exercise development was tailored to the conditions and characteristics of children, because between one child and another child was different. The progress of motor sensory training had five subjects and all of which had different characteristics of ability. The progress or speed in responding to their exercise stimulation was affected by age, environmental stimulation, and home-based exercise. Keywords: Intervention, Sensory-motor Exercise, Autistic Children